Role of Muscle Mass and Nutritional Assessment Tools in Evaluating the Nutritional Status of Patients With Locally Advanced Nasopharyngeal Carcinoma - Pan, Xi; Liu, Hong; Feng, Guo; Xiao, Jie; Wang, Meng; Liu, Hua; Xie, Xueyi; Rong, Zhipeng; Wu, Jinru; Liu, Min (Frontiers in Nutrition, 2021)
Objective: This study was to explore the role and necessity of muscle mass [fat-free mass index (FFMI) and appendicular skeletal muscle index (ASMI) measured by bioelectrical impedance analysis (BIA)] in nutritional status evaluation of patients with locally advanced (Ⅲ，Ⅳa) nasopharyngeal carcinoma (NPC). Methods：One hundred and thirty locally advanced NPC patients were recruited. Their nutritional status was assessed by albumin (ALB), body mass index (BMI), Nutritional Risk Screening 2002 (NRS 2002), Patient generated- Subjective Global Assessment (PG-SGA) and muscle mass. Consistency test and McNemar test were used to evaluate the consistency of muscle mass with ALB, BMI, NRS 2002 and PG-SGA, and correlation analysis was performed on muscle mass and PG-SGA or BMI. Results: 61/130 (46.9%) of the patients had nutritional risks according to NRS 2002, 68/130 (53.1%) of the patients had malnutrition according to PG-SGA assessment. FFMI and ASMI could determine the loss of muscle mass that cannot be detected by albumin (30.2% and 65.6%), BMI (28.0% and 35.3%), NRS 2002 (26.1% and 25.0%) and PG-SGA (18.6% and 55.6%). McNemar test showed that the malnutrition results assessed by FFMI and BMI were inconsistent (P <0.001), but further Pearson correlation analysis showed that BMI was positively correlated with FFMI (rs= 0.300, P = 0.001). Conclusion: The commonly used nutritional assessment scale/parameters cannot identify the muscle mass loss in patients with locally advanced NPC. Analysis of human body composition is important for nutritional assessment in patients with locally advanced NPC.